2012
DOI: 10.1103/physrevlett.108.263003
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond Time-Resolved Imaging of Molecular Structure by Photoelectron Holography

Abstract: Dynamic imaging of the molecular structure of H(2)(+) is investigated by attosecond photoelectron holography. The interference between direct (reference) and backward rescattered (signal) photoelectrons in attosecond photoelectron holography reveals the birth time of both channels and the spatial information of molecular structure. This is confirmed by simulations with a semiclassical model and numerical solutions of the corresponding time-dependent Schrödinger equation, suggesting an attosecond time-resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
115
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 17 publications
1
115
0
Order By: Relevance
“…its frequency. Because of their high energy, in contrast with that of direct electrons which is 2U p , RE can be used as signal and DE as reference to image atomic and molecular structure by photoelectron holography [20,25].Compared to atoms, the study of strong-field electron dynamics in molecules, in particular ionization, offers a richer perspective due to the additional degrees of freedom associated with the nuclei. Indeed, several phenomena due to the multicenter character of the molecular potential have already been discovered, such as charge-resonanceenhanced ionization [26] and light-induced-electron diffraction [27][28][29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…its frequency. Because of their high energy, in contrast with that of direct electrons which is 2U p , RE can be used as signal and DE as reference to image atomic and molecular structure by photoelectron holography [20,25].Compared to atoms, the study of strong-field electron dynamics in molecules, in particular ionization, offers a richer perspective due to the additional degrees of freedom associated with the nuclei. Indeed, several phenomena due to the multicenter character of the molecular potential have already been discovered, such as charge-resonanceenhanced ionization [26] and light-induced-electron diffraction [27][28][29].…”
mentioning
confidence: 99%
“…its frequency. Because of their high energy, in contrast with that of direct electrons which is 2U p , RE can be used as signal and DE as reference to image atomic and molecular structure by photoelectron holography [20,25].…”
mentioning
confidence: 99%
“…Eq. (10) shows that in general these two processes interfere for a given asymptotic electron momentum (k x , k y ). It has been shown that large electron energies (and thus small de Broglie wavelengths able to resolve sub-Å spatial scales) are reached by electrons ionized around a maximum of the field [26].…”
Section: Simplified Analytical Model Based On Sfamentioning
confidence: 99%
“…Since then, several theoretical and experimental LIED related studies were performed in order to image time-resolved dynamics of molecular systems [5][6][7][8][9]. Closely related to LIED is the attosecond photoelectron holography imaging idea, again pioneered by A. D. Bandrauk and coworkers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the laser technology, the interaction between the intense laser pulses and the atoms [1,2] or the molecules [3,4] becomes an issue of wide interest and has received a lot of attention. High-order harmonic generation (HHG) as one of the most important nonlinear phenomena has been investigated for many years due to its potential applications in the generation of coherent UV attosecond pulses [5,6] and in the time-resolved dynamics measurement of the atomic/molecular structure [7].…”
mentioning
confidence: 99%